Different serotonin type 3 subunit can coassemble into heteromeric receptors - Corradi, Jeremias (2018)
5-HT3 receptors are the only serotonin (5-HT) receptors that belong to the Cys-loop receptor family. They mediate fast excitatory transmission in central and peripheral nervous system. Five different subunits (A-E) have been identified in humans. The A subunit is able to form functional homomeric receptors (5-HT3A), and it can also combine with the B subunit to form heteromeric receptors (5-HT3AB). To evaluate the capability of the C, D and E subunits to combine with the A subunit to form heteromeric receptors we performed single-channel and macroscopic recordings. After expression of the A subunit, we recorded single-channel openings with an amplitude corresponding to the 5-HT3A receptor. However, when this subunit was expressed with one of the C-E subunits, opening events with different amplitudes were detected, thus confirming the expression of heteromeric receptors. From macroscopic currents we determined that the EC50 values for 5-HT were statistically different when homomeric or heteromeric receptors were expressed. Taking together, our results demonstrate that all the 5-HT3 subunits can combine with the A subunit to form heteromeric receptors. In-silico studies provided insights into the contribution of the different subunits to the 5-HT binding site. The functional characterization of different heteromeric 5-HT3 receptors will contribute to the development of selective therapies targeting this receptor family